2017
DOI: 10.1016/j.nmni.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GeneXpert MTB/RIF for determination of rifampicin resistance among new tuberculosis cases in west and northwest Iran

Abstract: Despite a Mycobacterium tuberculosis control programme and anti-tuberculosis drugs, drug-resistant tuberculosis (DR-TB) is one of the most serious public health issues worldwide. Rapid laboratory diagnosis of M. tuberculosis is needed for the diagnosis of multidrug-resistant (MDR) TB and to find the optimal treatment protocol. The purpose of this study was to detect resistance to rifampicin in new cases of TB using the GeneXpert MTB/RIF (M. tuberculosis/rifampicin) assay and the standard proportional method in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
0
22
1
Order By: Relevance
“…When comparing the Xpert results of the 103 samples to their pDST results, Xpert had a sensitivity of 91.1%, speci city of 79.2% (Table 3). The agreement rate between pDST and Xpert was 88.3%, which is lower than the previously reported Xpert performance [9,10].…”
Section: Xpert Vs Pdstcontrasting
confidence: 78%
“…When comparing the Xpert results of the 103 samples to their pDST results, Xpert had a sensitivity of 91.1%, speci city of 79.2% (Table 3). The agreement rate between pDST and Xpert was 88.3%, which is lower than the previously reported Xpert performance [9,10].…”
Section: Xpert Vs Pdstcontrasting
confidence: 78%
“…In this study, conventional drug susceptibility test and Xpert assay were used for characterizing the RIF resistance; however, we did not find any resistant isolates, which limited our ability to evaluate the efficiency of the Xpert assay for the identification of RIF resistance. In a study conducted on ten provinces located in the west and northwest of Iran, the sensitivity and specificity of the Xpert assay for the determination of the RIF resistance were 71% and 100%, respectively (22). As the RIF resistance was uncommon in Golestan Province, 0.5% for new TB cases (8), additional research is recommended with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Indonesia has shown a high sensitivity (89-93%) and specificity (81-92%), suggesting that the Xpert® MTB/RIF could be used as a diagnostic tool for ruling out TB or MDR-TB in Indonesia as one of the countries with a high TB burden.8 An effective TB treatment requires an accurate and early diagnosis as well as screening for drug resistance and HIV, which should be done with a low testing cost per sample. 17 Thus, new TB cases can directly benefit from the use of this Xpert® MTB/RIF examination.…”
Section: Figure Distribution Of Mdr Tb Patients From Various Regions In West Java Indonesiamentioning
confidence: 99%